Planning for the 1970's Higher Education in Colorado. - Colorado Commission on Higher Education, Denver; Colorado Commission on Higher Education, Denver ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This statement deals with the possibilities, the planning, and the policies that will bring higher education and its participants in Colorado through the 70's and into 1980. The number of college-age students has increased rapidly in Colorado during the 1960's and the incline is expected to be even greater in the 70's. This Commission report is designed to: (1) assess the needs of institutions in the 1970's; (2) plan for accommodating students; (3) plan for growth within the programs of the institutions; (4) aid the development of higher education in metropolitan areas; (5) review coordination, planning, and governance of higher education in Colorado; and (6) estimate the costs of this expanding system. The Commission issues this report with acute awareness of limitations both in scope of the report and in the processes of involvement of interested parties in its development. (HS)
ERIC Note: Revised Oct 1971.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Budgeting; Educational Administration; Educational Planning; Higher Education; Planning; Policy Formation